Linkages and Multipliers of the Agricultural Sector in the Regional Economy in Tanggamus Regency: Input-Output Analysis - Muhammad Irfan Affandi; Fadhilah Ismi Badai; I Wayan Suparta (Eduvest - Journal of Universal Studies, 2023)
One of the regional developments carried out is development in the agricultural sector. Development in agriculture is expected to be a catalyst in achieving the goal of increasing the regional economy. This study aims to analyze the linkages and multipliers of the agricultural sector to the regional economy in Tanggamus Regency. The method used is input-output analysis which consists of linkage analysis, dispersion impact, and output and income multiplier effect. The results of the analysis conclude that the agricultural sector has a linkage to the manufacturing sector in the future; and the transportation and warehousing sector, then has backward linkages with the real estate sector and the construction sector. The agricultural sector is able to drive production growth in the downstream industrial sector. The output multiplier and income multiplier of the agricultural sector has a lower value compared to other economic sectors.